Campus study buddy: Collaborative learning and resource sharing app - Huang, Yifan (2024)
The trend of modernization and digitization of education is developing. Today, many educational institutions are using learning management systems to improve their operational efficiency. However, most of the existing learning management systems focus on improving the administrative and teaching capabilities of educational institutions, and lack the encouragement of students' collaborative learning and the ability to improve students' learning motivation. This project is aiming to create a mobile application based on Android. Higher education institutions can use this program to provide students with a platform to collaborate and support each other's learning, creating a collaborative learning environment, promoting knowledge sharing, and improving student academic success. The application is developed using Flutter and uses a tag recommendation algorithm to push content that users may be interested in, thereby intelligently providing users with an online learning environment that suits them and improving their learning efficiency. Compared with other LMS, this application provides more interactive social elements and a resource directory that facilitates students' campus life. An incremental development approach is adopted in the project. The final deliverable of the project is an Android mobile application that integrates Google Cloud and Google Firebase while providing basic functions. The delivered application allows users to get started quickly and allows students to use it as a learning companion to enhance the learning experience. It is also highly customizable, allowing the system to quickly adapt to organizational requirements.